Laporan Kasus: Diagnosis dan Tatalaksana Meningoensefalitis Tuberkulosis dan Ensefalitis Toksoplasma pada Pasien dengan HIV Positif - Della Septa; Yudhisman Imran; Ronny Yoesyanto Pragono (Jurnal Biomedika dan Kesehatan, 2022)
Background Tuberculous meningoencephalitis (TBME) and toxoplasma encephalitis (TE) are the most frequent cerebral opportunistic infections in positive HIV patients in developed countries. This study aims to determine a presumptive diagnosis of TBME and TE based only on clinical, CD4-count, and radiology features and to attend suitable early treatment for better patient outcomes. Case Description A 40-year-old presented to the emergency unit of dr. Mintohardjo Naval Hospital with decreased consciousness. History of positive HIV status, pulmonary tuberculosis for six months and anti-tubercular-treatment (ATT) drop-out. The GCS was E2M5V2, lung crackles, nuchal rigidity, positive Babinski reflex, and duplex hemiparesis. CD4-count: 4 cells/mm3. Multiple hypodense lesions, “finger-like-oedema”, featured on non-contrast head CT-scan. A lumbar puncture was not performed. Treatment of TBME included an ATT regimen, pyridoxine, cotrimoxazole, anti-oedema, and TE treatment included clindamycin and pyrimethamine. Based on the clinical and radiological diagnosis of TBME (nuchal rigidity, history of ATT drop-out, multiple hypodense lesions on CT-scan) and TE (altered mental status, duplex hemiparesis, CD4-count, “finger-like-oedema” projections on CT-scan), ATT and TE treatment were given for ten days. There were significant clinical improvements by GCS E4M6V3, negative nuchal rigidity after being treated early by ATT and TE treatment. Conclusions Presumptive Diagnosis of TBME and TE in HIV patients can be determined only based on clinical, CD4-count, and radiology examination. However, there are significant clinical improvements in giving ATT along with TE treatment immediately in positive HIV patients.